BESAR RISIKO PENYEBAB LANGSUNG TERHADAP KEJADIAN KEP PADA BALITA DI KECAMATAN PLERET KABUPATEN BANTUL TAHUN 2010 - Tuti Rohani (MIKKI (Majalah Ilmu Keperawatan dan Kesehatan Indonesia), 2014)
ABSTRACTBackground: Nowadays, Indonesia is facing four main nutrient problems, i.e. Lack of Energy and Protein (KEP) in the children under five, Lack of vitamin A in the children under five, lack of iodine value and anemia. The causes of AKB and AKBA in Indonesia are found in the neonatal period and the cause of contagious disease especially pneumonia, malaria and diarrhea, worsen with the nutrient problem that can cause 80% of children death.  The objective of the research: To know the value of direct risk of KEP Lack of Energy and Protein in the children under five at Pleret, Bantul Regency in the year of 2010. Research method: This research was the observational research with the cross sectional desihn. This research  was done to know the value of direct risk in the KEP case in Pleret, Bantul Regency in the year of 2010. The  subjects of the research were the children under five in the age of 12-59 months with the food recall form for 24 hours to measure the consumption of energy and protein. The checklist form was to know the identity and the characteristics of the respondents with the interview guide. The tool to know the weight were a pair of scales called Dachin with the minuteness 0,1 kilogram to measure the children’s weights. To know the correlation between independent variable and dependent variable the researcher used chi-square test and then the factors that had correlations were analyzed to know the risk value, were tested with the relative risk and prevalence risk. The results of the research: the children under five in Pleret in the year of 2010 according to the protein intake in the research subjects were mostly adequate that is 81,7% (147 children). The children under five who have protein intake in adequate value is (89,1%) and they are far from KEP. Whereas the children under five with the less protein intake suffer KEP (48,5%). The statistics show that there are defferences between the energy, protein, and the diseaase data record in the children under five with the KEP status and non KEP i.e. (p<0,05).Conclusion: the disease data record of serious illness, the calorie intake, protein intake have the correlation in the KEP case in the children under five. The availability of foods and the BBLR disease data record, the immunization status, the breast feeding record, sanitation of the family have the effect of KEP in the children under five. The direct factor has prevalence risk 5 up to 7 higher to get KEP in the children under five.